Sustainable nanomaterials: the role of Cyrene in optimising carbon nanotubes dispersion and filtration efficiency - Milescu, Roxana A.; McElroy, C. Rob; Taylor, Edward J.; Eaton, Peter; Williams, Paul M.; Phillips, Richard; Farmer, Thomas J.; Clark, James H. (Frontiers in Chemistry, 2024)
This study investigates the fabrication and characterisation of single-walled carbon nanotube (SWCNT) buckypapers for the first time and polyethersulfone (PES) flat-sheet membranes using Cyrene, a bio-based and environmentally friendly solvent, as an alternative to N-Methyl-2-pyrrolidone (NMP). Pristine SWCNTs were successfully dispersed in Cyrene without surfactants, achieving higher concentrations (0.038 mg mL⁻¹) compared to NMP (0.013 mg mL⁻¹). TEM analysis demonstrated that Cyrene effectively debundles SWCNTs, achieving better dispersion than NMP. The resulting buckypapers exhibited dense, uniform SWCNT networks with enhanced surface smoothness when fabricated using Cyrene. These materials showed promising performance in wastewater treatment and oil-water separation applications. PES flat-sheet membranes incorporating SWCNTs were also produced, with Cyrene-based membranes displaying distinct morphological characteristics, including well-organized finger-like structures and interconnected pores. PES membranes fabricated using Cyrene exhibited superior porosity, higher water permeability, and more organised pore structures compared to those made with NMP, with SWCNTs further enhancing performance. While bacterial challenge tests showed no significant antimicrobial activity, the membranes' versatility in various filtration ranges (nanofiltration to microfiltration) at lower operating pressures highlights their potential for diverse applications. This research demonstrates the viability of Cyrene as a sustainable alternative to traditional solvents in membrane and buckypaper fabrication, although further investigation of solvent residuals and safety considerations is warranted.